Two new species of Cassida Linnaeus, 1758 (Coleoptera: Chrysomelidae: Cassidinae) from Madagascar and notes on subgenera of the genus Cassida - Borowiec, Lech (Zootaxa, 2007)
Cassida butterwecki sp. nov. and Cassida morondaviana sp. nov. are described from Madagascar. Both are unique species and have no close relatives in Madagascar or tropical Africa. Subgeneric division of the genus Cassida Linnaeus, 1758 is discussed.